Analysis of the Quality of Health Service at the Air Haji Hearth Center Using the Ordinal Logistics Regression Method - Soleha, Annisa; Sari, Devni Prima (UNIB Press, 2024)
Improving the quality of public services has become a major concern in government agencies as an effort to provide optimal public services. The quality of service can be affected by various factors. Therefore, it is necessary to conduct an analysis to find out the relationship between factors that affect service quality and service quality itself. Efforts are made to analyze the relationship between factors that affect service quality and service quality itself by using the ordinal logistic regression method in analyzing the relationship between influencing factors and influencing factors. This type of research is applied research that begins with theoretical analysis and data collection then ordinal logistic regression analysis. Based on the results of data analysis, it was found that the variables that significantly affected the quality of service were direct evidence variables, guarantee variables, and empathy variables. This research is useful for the Air Haji health center in an effort to improve the quality of health services.